2011
DOI: 10.1007/s00125-011-2355-6
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of 31 common polymorphisms with type 2 diabetes and its related traits in Indian sib pairs

Abstract: Aims/hypothesisEvaluation of the association of 31 common single nucleotide polymorphisms (SNPs) with fasting glucose, fasting insulin, HOMA-beta cell function (HOMA-β), HOMA-insulin resistance (HOMA-IR) and type 2 diabetes in the Indian population.MethodsWe genotyped 3,089 sib pairs recruited in the Indian Migration Study from four cities in India (Lucknow, Nagpur, Hyderabad and Bangalore) for 31 SNPs in 24 genes previously associated with type 2 diabetes in European populations. We conducted within-sib-pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 44 publications
2
34
1
2
Order By: Relevance
“…This is further supported by the fact that numerous associations between SNP rs7578597 in THADA and type 2 diabetes related traits have been observed in other populations [54, 55]. In our Mexican American population, we observed a nominal association with prediabetes, reaffirming the previous findings in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…This is further supported by the fact that numerous associations between SNP rs7578597 in THADA and type 2 diabetes related traits have been observed in other populations [54, 55]. In our Mexican American population, we observed a nominal association with prediabetes, reaffirming the previous findings in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…23 Another study has shown association of 31 common polymorphisms with T2DM in Indian sib pairs. 24 The association between CD36 gene overexpression and presence of atherosclerotic risk factors, particularly diabetes, shown in this study is in agreement with a common etiology of the disease. 25 The role of the CD36 protein in lipid metabolism and metabolic syndrome prompted us to investigate the association of CD36 gene variants with T2DM.…”
Section: Discussionsupporting
confidence: 82%
“…Cxcr4, Pask, Cntnap5a, Lct, and Pik3c2b are positional candidate genes for Bglu12 . Variants of these genes have been found to be associated with susceptibility to T2DM, fasting glucose, or insulin resistance in humans 62, 63,64, 65, 66, 67 .…”
Section: Discussionmentioning
confidence: 99%